Energy-Efficient Adaptive Dynamic Building Facades: A Review of Their Energy Efficiency and Operating Loads - Nurlan Zhangabay; Timur Tursunkululy; Ulzhan Ibraimova; Uliya Abdikerova (Applied Sciences)
Energy-efficient, adaptive, affordable and durable curtain wall systems have always attracted great interest among the scientific and technical communities. In this regard, the purpose of this work was to conduct a comprehensive review of the issues related to energy-efficient adaptive dynamic facades, taking into account their operating loads, revealing the diversity of the studies conducted in this area. The review of the literature was carried out in three stages. For all stages, the review period was 2001–2024. In the first stage, a review of traditional curtain facade systems was conducted, which emphasized the relevance of this area, identifying a total of 4338 sources. In the second stage, a review of specific issues, such as adaptive dynamic facade systems, yielded 2838 sources, from which the 87 most suitable sources were selected. In the third stage, a review focusing on the issue of operating loads yielded 741 works, from which 43 suitable sources were selected. At the same time, pie charts reflecting the most active international scientific journals were compiled for each area. The conducted review of energy-efficient adaptive dynamic building facades, taking into account their operating loads, could provide significant assistance in further research on the specified issues. As researchers mainly focus on environmental friendliness and cost-effectiveness, they often neglect issues such as the systems’ resistance to operating loads, which represents a serious deficiency. In this regard, this review identified a gap in the research on the development of energy-efficient facades with an air layer; on this basis, the further development of adaptive facade systems is required. The review of the selected studies also showed that issues related to energy efficiency and sustainability, taking into account operational loads, have not been addressed in combination; rather, they have only been addressed individually. At the same time, this review shows that the proposed development of an adaptive system of external fencing could be relevant, both nationally and internationally, depending on the natural and climatic conditions of the territory for which the buildings are designed.